2024
DOI: 10.3390/photonics11030283
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Stilbene- and Azobenzene-Type Systems for Optical Frequency Conversion: Estimating the First-Order Molecular Hyperpolarizability

Raiane S. Araújo,
José J. Rodrigues,
Márcio A. R. C. Alencar
et al.

Abstract: This study investigates the potential of a set of pseudo-stilbene and azobenzene molecular structures to become optical frequency converters for optical communications based on a detailed exploration of the first-order molecular hyperpolarizability (βHRS), which is the microscopic counterpart of second harmonic generation (SHG). βHRS values were obtained via quantum chemical calculations using the Gaussian 16 software package in solvent and gas-phase media at different wavelengths, i.e., 1064 nm, 1310 nm, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Abegăo et al explored new push–pull derivatives that simultaneously integrate pseudo-stilbene and azobenzene units in their molecular structures. 32 Their work showcasted the potential of this novel molecular design for applications in photonic crystals with NLO conversion capabilities. Previous research has demonstrated that strong charge transfer can significantly enhance the NLO response by influencing the dipole moment and hyperpolarizability of molecules.…”
Section: Introductionmentioning
confidence: 98%
“…Abegăo et al explored new push–pull derivatives that simultaneously integrate pseudo-stilbene and azobenzene units in their molecular structures. 32 Their work showcasted the potential of this novel molecular design for applications in photonic crystals with NLO conversion capabilities. Previous research has demonstrated that strong charge transfer can significantly enhance the NLO response by influencing the dipole moment and hyperpolarizability of molecules.…”
Section: Introductionmentioning
confidence: 98%